Traffic engineering handbook - Pande, Anurag; Wolshon, P. Brian (Paul Brian); Institute of Transportation Engineers (Hoboken, New Jersey : John Wiley & Sons Inc., 2015)
'The Traffic Engineering Handbook is a comprehensive practice-oriented reference that presents the fundamental concepts of traffic engineering, commensurate with the state of the practice'--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Traffic engineering -- Handbooks, manuals, etc; Electronic books